The Interplay of Work-Life Balance and Job Stress in Shaping Organizational Commitment: Evidence from the Hospitality Sector - Budi Iriani Yudaningrum; Alwin Lasarudin; Dita Rachmawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of Work-Life Balance (WLB) and Work Stress on Organizational Commitment among employees in the hospitality sector. A quantitative study with a cross-sectional survey approach was conducted on 110 employees from various departments in 4 and 5-star hotels in Malang. Data were collected using an online questionnaire containing scales for Work-Life Balance (10 items, adapted from Haar et al., 2019), Work Stress (10 items, adapted from Perceived Stress Scale, Cohen & Williamson, 1988), and Affective Commitment (8 items, adapted from Allen & Meyer, 1990). Data were analyzed using multiple regression analysis with SPSS. The results show that Work-Life Balance has a positive and significant effect on Organizational Commitment (β = 0.349, p < 0.001). Conversely, Work Stress has a negative and significant effect on Organizational Commitment (β = -0.342, p < 0.001). Both variables collectively explain 82.4% of the variance in Organizational Commitment (Adj. R² = 0.824). These findings highlight the importance of WLB and stress management in enhancing employee commitment in the hospitality industry.